Longitudinal analysis of perfusion lung scintigrams of patients with unoperated chronic thromboembolic pulmonary hypertension - Skoro-Sajer, Nika; Becherer, Alexander; Klepetko, Walter; Kneussl, Meinhard P.; Maurer, Gerald; Lang, Irene M. (Thrombosis and Haemostasis, 2004)
Chronic thromboembolic pulmonary hypertension (CTEPH) is the result of single or recurrent pulmonary thromboemboli that are thought to develop into organized pulmonary arterial obstructions by recurrent embolism and in situ thrombosis. Radioisotopic ventilation-perfusion scanning (V/Q scan) is a safe and highly sensitive test for pulmonary thromboembolic disease. The aim was to assess the natural history of thrombus expansion. We performed a prospective quantitative evaluation of ventilation/perfusion scintigrams (V/Q scans) in 20 patients with severe unoperated CTEPH. The baseline V/Q scan of each patient served as a reference for the second scan 21.7 ± 8.2 months later. Planar images with intravenous 99mTc-labeled human albumin macroaggregates were reconstructed in six standard projections. Perfusion scans were analyzed by a semiquantitative evaluation. In parallel, hemodynamics and clinical condition were prospectively observed. Lung perfusion scintigrams analyzed by a semi-quantitative method in patients with severe unoperated CTEPH show an apparent decrease of segmental flow abnormalities over time, paralleling right ventricular decline.
Keywords: Pulmonary embolism; perfusion lung scintigraphy; thrombosis; pulmonary hypertension